Impacts of photovoltaic power source intermittence on a distribution network - Oumaima Garfi; Helmi Aloui; Nadia Chaker (International Journal of Electrical and Computer Engineering (IJECE), 2019)
The integration of the photovoltaic (PV) solar systems into distribution networks has brought new challenges to the network planners. One of the most interesting is to prevent the impacts of the PV intermittent character on the steady state system operation conditions. This work is aimed to investigate such effect on voltage performance, conventional generator daily behavior and automatic voltage regulator operation. Simulations were conducted on a 33-bus IEEE radial distribution power system. In order to provide a reliable study, a real PV power profile was considered. Obtained results over a period of 24 hours revealed that the PV integration contributes to an enhancement of the overall voltage profile, a considerable saving in the total amount of the produced active power and a reduction of power losses. However, the PV intermittent character causes significant transformation in buses voltages daily profiles as well as changes in production plan. To sum up, this paper reports the alterations, caused by the PV source intermittence, which must be taken into consideration by the distribution networks planners to maintain the overall network parameters within safe operating condition